Origin and haplotype diversity of the northernmost population of Podarcistauricus (Squamata, Lacertidae): Do lizards respond to climate change and go north? - Rehák, Ivan; Fischer, David; Kratochvíl, Lukáš; Rovatsos, Michail (Biodiversity data journal, 2022)
The northernmost population of the Balkan wall lizards, Podarcistauricus (Pallas, 1814) was recently discovered in the Czech Republic. We studied genetic variability in a mitochondrial marker cytochrome b to shed light on the origin of this remote population. We detected three unique haplotypes, close to those occurring in the populations of Podarcistauricus from central/north Balkans and Hungary. Our data exclude the hypothesis of a single founder (a randomly or intentionally introduced pregnant female or her progeny) of the Czech population and indicate a native, autochthonous origin of the population or recent introduction/range expansion.
Keywords: introduction; cytb; new haplotypes; Czech Republic; autochthonous population; Podarcistauricus; wall lizards